The Benefits of Joining English Speaking Club as an Extracurricular Activity : A Case Study at MA Patra Mandiri Plaju - Jenni Septi Liana; Renny Kurnia Sari; Mirrah Salsabila (The Explora, 2024)
This research investigated the benefits of joining English speaking club as an extracurricular activity. The study aimed to find out the benefits of joining English club on students' speaking ability. The study used a qualitative research approach, and data was collected using interview. The participants were five eleventh-grade students who had joined the English club, one boy and four girls. The study found that there were 4 benefits gained by joining the English club. They are, The English club was more enjoyable than regular classes, the students received moral and emotional support to became confident, they got the same turn to speak, and they got new vocabulary. In short, the English club was a place for students to improve their English speaking skills and also a place for those who were interested to join many English competitions.